The lysine response of the turkey - Nixey, Clifford (1991)
After reviewing the literature, it was found that there was a paucity of information on the subject. Examination of quantitative models of nutritional responses of a turkey did not clarify the situation. Analysing suitable published data by the Reading flock response model (Fisher, Jennings and Moms, 1973), which derives the two constants a and b in the equation:- Lysine requirement = a x body-weight gain + b x body-weight showed some agreement in a values among different experiments, although b values varied greatly.